Analysis Of Patients Suggested With Dengue Fever Based On Hematological Characteristics At Pirngadi Hospital, Medan City - Jenny Ria Sihombing; Stephanie Salim; Nathalia Elizabeth Rouli Sipahutar (Sean Institute, 2023)
Cases of dengue hemorrhagic fever in Indonesia fluctuate every year and tend to increase in morbidity and spread to a wider area of ​​infection. The purpose of this study was to determine the routine hematological characteristics of dengue hemorrhagic fever patients at Dr. Pirngadi city of Medan for the 2020-2022 period. The research method used was a descriptive cross-sectional research method with a sample of 93 people. The sample was obtained by the medical records of RSUD Dr. Pirngadi. The results of the study: The most age of dengue hemorrhagic fever sufferers was <20 years 46 people (49.5%), the most sex was male 57 people (61.3%), and the most occupation was not working 53 people (57%). The highest hemoglobin count was normal 65 people (69.9%), the highest erythrocyte count was normal 72 people (77.4%), the highest hematocrit was normal 50 people (53.8%), the highest leukocytes were normal 56 people (60.2%) The highest number of platelets decreased by 90 people (96.8%), the most basophils were normal 93 people (100%), the most eosinophils were normal 92 people (98.9%), the most neutrophils were normal 46 people (49.5%), the most monocytes was an increase of 61 people (65.6%), the most normal lymphocytes were 66 people (71%).